2022
DOI: 10.1186/s11658-022-00406-9
|View full text |Cite
|
Sign up to set email alerts
|

Exosomal miR-628-5p from M1 polarized macrophages hinders m6A modification of circFUT8 to suppress hepatocellular carcinoma progression

Abstract: Background Hepatocellular carcinoma (HCC) is the most common type of liver cancer. CircFUT8 has been shown to be upregulated in cancers, but its function in HCC remains unclear. Tumor-associated macrophages (TAMs) are one of the main components of the tumor microenvironment (TME), and M1 macrophages function as tumor suppressors in cancers. Exosomes exert an important role in the TME, and circRNAs can be modified by m6A. We investigated the function of circFUT8 in HCC and its interaction with e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
27
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 47 publications
(27 citation statements)
references
References 32 publications
0
27
0
Order By: Relevance
“…As the most abundant RNA modification, m6A modification displays vital and different biological functions in multiple tumor progression [ 26 , 35 37 ]. Although studies revealed that the m6A methyltransferase exhibits oncogenic activity in DLBCL [ 20 , 38 ], there is little direct evidence showing other modulators as oncogenic or tumor suppressive effects.…”
Section: Discussionmentioning
confidence: 99%
“…As the most abundant RNA modification, m6A modification displays vital and different biological functions in multiple tumor progression [ 26 , 35 37 ]. Although studies revealed that the m6A methyltransferase exhibits oncogenic activity in DLBCL [ 20 , 38 ], there is little direct evidence showing other modulators as oncogenic or tumor suppressive effects.…”
Section: Discussionmentioning
confidence: 99%
“…Therapeutic targeting of UCK2 and its downregulation may lead to an increase in cancer immunity in HCC [ 28 ]. Since molecular interactions play a key role in HCC progression [ 29 , 30 ], the current review was dedicated to understanding the function of STAT3 signaling in HCC tumorigenesis.…”
Section: Introductionmentioning
confidence: 99%
“…Macrophage exosomal miRNAs have also been reported to affect tumorigenesis. For instance, M1 macrophage-derived exosomal miR-628-5p inhibits the development of hepatocellular carcinoma [ 15 ], whereas M2 macrophage-derived exosomal miR-3917 promotes the progression of lung cancer [ 16 ]. M2 macrophage-derived exosomal miR-21-5p, miR-155-5p, miR-221-5p, and miR-501-3p promote the differentiation and activity of PC stem cells [ 17 ] and the growth, angiogenesis [ 18 ], migration, and invasion of PC cells [ 19 ].…”
Section: Introductionmentioning
confidence: 99%